The Development and Fate of Vilnius University Professors’ Personal Libraries in 1803–1832: Current Research Areas - Pacevičius, Arvydas (Knygotyra, 2025)
The article examines the circulation of the book collections of professors of Vilnius Imperial University in academic and urban culture in 1803–1832 from the aspect of the legacy of personal libraries. The aim is to determine how the elite of the academic community treated their intellectual property in everyday life and in the face of social and existential challenges, as well as to clarify relevant research directions for personal libraries in early modernity. The work distances itself from the dissemination of book heritage in the second half of the 19th century and the 20th century. The aim of the research is to discuss the origin and culture of inheritance of the professors’ personal libraries, the circulation of books in the academic space and the secondary book market, after systematizing data on the nature and scope of the collections. It has been established that the professors’ libraries – in parts or in corpore – were not only donated to the University (in cases of A. Abicht, A. Bécu, M. Mianowski, M. Poliński, A. Śniadecki, J. Twardowski, J. Wolfgang) or bequeathed to the University in wills (in cases of J. K. Chodani, W. Herberski, J. Śniadecki), but were also sold to the University (in cases of A. Bécu, L. Bojanus, G. Groddeck, I. Danilowicz, J. Lelewel, J. Lobenwein, I. Oldachowski, R. Symonowicz, S. Stubielewicz); books were also exchanged with the Alma Mater (in cases of I. Daniłowicz, J. Jundziłł, J. Lelewel, I. Onacewicz, M. Poliński), and collections were also inherited by relatives (in cases of J. Abicht, L. Bojanus, G. Groddeck, J. Jundziłł, Z. Niemczewski, F. Smuglewicz). In the event of death, solid compensation was paid to the professors’ families – A. Bécu, J. Lobenwein, S. Stubielewicz, etc., members for the personal libraries sold to the University. Books were sold at auctions less frequently (in cases of J. Frank, J. Mickiewicz, W. Znamierowski); therefore, the dissemination of the professors’ collections in the wider, non-academic reading community, including export abroad, was limited – which was due to the University’s reluctance to share intellectual resources, the underdeveloped secondary book market, and the insufficient auction system in the city of Vilnius.
Keywords: professors; personal library; book collection; stationary trade; secondary book market; auction; wills; purchases; donations; inheritance